Use of digital tools to strengthen technical support processes in Mexico, Guatemala, and Honduras - Ovando, Rausel; Jiménez, Benancio; May Tzun, Vladimir Nikolai; Martinez Perez, Gabriel; Odjo, Sylvanus; Van Loon, Jelle; García Santiago, Jorge Octavio; Espinosa Diaz, Anabell Guadalupe (CIMMYT, 2025)
This document presents the results and lessons learned from the implementation of the Scaling for Impact science program, which aims to integrate and assess in situ digital technology packages to accelerate the adoption of sustainable agricultural practices through comprehensive technical assistance supported by digital tools and digitized agricultural machinery services. The intervention was led by CIMMYT within the CGIAR framework, combining territorial technical assistance methodologies with the development and deployment of digital platforms designed to enable scaling. The report is structured around two main components. The first documents the technical assistance methodology of the Innovation Hub model, implemented in Mexico, Guatemala, and Honduras. This model integrates participatory diagnostics, co-design of innovations, field-based validation, and adaptive learning processes. Its implementation is supported by the digital platform e-Agrology, which is used for the standardize registration of agronomic information, the monitoring of practices and innovations, and the generation of technical, economic, social, and environmental evidence to inform decisionmaking and support territorial scaling. In 2025, the implementation of the model enabled the establishment of a physical infrastructure covering 39,691.7 hectares and benefited 30,832 producers across the three countries. These results demonstrate the multiplier effect of technical assistance when it is articulated through local networks of partners, extension agents, and public programs. The use of eAgrology strengthened the traceability of interventions, the systematization of results, and the visibility of impact, enabling scaling processes that extend beyond the physical reach of direct field interventions. The second component of the document presents the experience of designing, implementing, and validating Tractilus, a digital platform focused on the planning, logistics, monitoring, and management of gricultural machinery and input services, developed and piloted in Mexico. Between 2022 and 2025, Tractilus evolved from field-based needs assessments to the deployment of a native mobile application, validating its technical, operational, and social feasibility in the states of Aguascalientes, Zacatecas, Hidalgo, and Guanajuato. The platform enabled the registration of producers, service providers, plots, and serviced areas, generating a strategic database to organize the supply and demand of machinery services. Overall, the results confirm that the integration of digital tools with face-to-face technical assistance schemes constitutes an effective mechanism to accelerate the adoption of sustainable innovations, improve operational efficiency, and enable scaling. The evidence generated positions digital platforms as key instruments for expanding the reach of interventions, strengthening data-driven decision-making, and contributing to the design of public policies and replicable model in other territories.